Penggunaan Media Sosial (Instagram) dalam Promosi Kesehatan Gigi dan Mulut terhadap Peningkatan Pengetahuan pada Pasien Usia Sekolah tentang Kesehatan Gigi dan Mulut di Puskesmas Minasa Upa - Hasrini Hasrini; Pariati Pariati; Zulkarnain Zulkarnain; Amirah Maritsa; Zahrawi Astrie Ahkam (Jurnal Sains dan Kesehatan, 2022)
Knowledge of how to maintain proper dental health will greatly Affects theincidence of dental caries, brushing and rinsing teeth - gargling is one of the behaviors to maintain oral hygiene. behavior based on correct knowledge will last longer than behavior that is not based on knowledge, an effort to increase knowledge is through health education. Online media is one of the educational media to increase knowledge of dental and oral health. The type of research in this study is a comparative analysis or "causal-comparative". The sampling technique which was used is the quota sampling based on 100 people in Puskesmas Minasa Upa as the research location.The research variable was the online media instagram in increasing knowledge of caries. The statistical analysis which was used is the T-test to show the relationship of Instagram in increasing the knowledge.The result shows that there is a role for education through online media in increasing the knowledge of cavities.